Avaliação sócio - econômica – ambiental da atividade mineradora em Catalão e Ouvidor - Goiás - Oliveira, César Antonio de (2002)
A striking feature of human history is its reliance on natural resources for survival as a species and for improving the quality of life related to technological advances. Despite this understanding, traditional economic science has not conditioned working on such resources as one of its major analytical concerns about scarcity, in many cases subjugating them to the condition of "externalities." However, the last decades, characterized by the immense incorporation of natural resources and the aggregation of new regions to the world production circuit, have demanded that a new form of evaluation be established. The methods and methodologies have undergone changes in their scope of analysis, adding qualitative values ​​that were not considered fundamental, including issues of regional and environmental impacts. Regions gained prominence as carriers of natural resources of interest to the productive circuit, such as the micro-region around Catalão-GO, which has become one of the most important poles of economic and social growth in the state, supported by phosphate mining and niobium. This work aimed to evaluate the impacts, in the economic-social-environmental sphere, of the niobium mining activity on this region, to the expectation that this was one of the main responsible for the change of scenery, occurred in the last 30 years. Assessed impacts on amount and population profile; about the attraction to other economic activities; on the level of employment; on the educational aspects; about local infrastructure; about taxation; about culture; and about the environment. In conclusion, it was found that although there is a difficulty in isolating the niobium exploration from mining as a whole, since its growth occurred at the same time as phosphate exploration, it can be classified as an important regional component, as regards rarity, destination and participation in the world market. It was also found that the assessed impacts were substantial, altering the entire regional socio-economic profile, presenting a new structure with a solid continuity trend, even projecting the end of mining activity, unlike other regions that have historically stood out. mining and did not hold up.